2014
DOI: 10.1603/en13338
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence Densities of Annual Cicadas (Hemiptera: Cicadidae) Increase With Sapling Density and Are Greater Near Edges in a Bottomland Hardwood Forest

Abstract: The emergence densities of cicadas tend to be patchy at multiple spatial scales. While studies have identified habitat conditions related to these patchy distributions, their interpretation has been based primarily on periodical cicada species; habitat factors associated with densities of nonperiodical (i.e., annual) cicadas have remained under studied. This is despite their widespread distribution, diversity, and role as an important trophic resource for many other organisms, particularly within riparian area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…Consistent with our results, other studies have shown high densities of cicada 163 nymphs in human-modified habitats, such as forest edges and plantations [30][31][32], 164 though the reasons are unclear (but see Yang [33]). This suggests that anthropogenic 165 habitat modifications provide high quality habitat for cicadas.…”
supporting
confidence: 87%
“…Consistent with our results, other studies have shown high densities of cicada 163 nymphs in human-modified habitats, such as forest edges and plantations [30][31][32], 164 though the reasons are unclear (but see Yang [33]). This suggests that anthropogenic 165 habitat modifications provide high quality habitat for cicadas.…”
supporting
confidence: 87%
“…As is the case in many restoration sites in California, many years of drought in the KRV and increased intensive farming up stream with deep well pumps and water diversions have resulted in decreased groundwater and lowered survival of seedlings that germinate from spring flooding (Gonzalez et al 2018). The lack of lower canopy vegetation volume from decreases in water inputs results in fewer nesting substrates and prey resources available to birds (Lite & Stromberg 2005; Chiavacci et al 2014). We propose that while reestablishment of overstory canopy is an important contribution to the recovery of Yellow‐billed Cuckoo and other sensitive songbirds, the processes necessary to develop a complex canopy structure and to sustain early successional habitat and potentially insect prey on the landscape through a time scale appropriate for early successional stage species are still missing throughout California and the western United States (Gonzalez et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Managers could reenter portions of these now mature impoundments and create openings to encourage germination of seeds or to plant new cottonwood and willow where flood irrigation is still feasible. Flood irrigation regularly throughout the season, as opposed to drip irrigation, mimics natural processes by recharging groundwater and promotes large insect prey abundance (Kirkpatrick et al 2009; Bunting et al 2013; Chiavacci et al 2014). Stump‐sprouting by felling mature trees can also augment regeneration density (Lite & Stromberg 2005; Gonzalez et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Invertebrates, which have higher numbers in dense young forest, prefer the vigorously growing, more nutritious leaves of younger, flowering willows and forbs for forage and oviposition sites (Reader & Southwood 1981; Raupp & Denno 1983; Chiavacci et al 2014; Tan et al 2017; Bentrup et al 2019). Willows are highly used by Lepidopteran species for egg laying (Tallamy & Shropshire 2009) and have higher nutritive value than other riparian species for insects (Bentrup et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Cuckoo populations respond positively in the first few years following planting and irrigation along the Lower Colorado River (LCR) and then decline after 6–10 years (McNeil et al 2019). Increased densities of small trees not only provide concealment for nests and newly fledged young (Paxton et al 2011), but may also provide more surfaces for increased densities of leaf‐ and flower‐foraging insect adults and larvae close to the nest (Chiavacci et al 2014; Tan et al 2017; Bentrup et al 2019). Young trees provide suitable nesting and egg‐laying sites for insects, and when they are close to flower‐rich foraging areas, insect densities increase (Bentrup et al 2019).…”
Section: Introductionmentioning
confidence: 99%